Environmental technology effect of two-way foreign direct investment interactive development in China - Gong, Mengqi; You, Zhe (Frontiers in Ecology and Evolution, 2022)
This paper examines the impact of the interactive development of inward foreign direct investment and outward foreign direct investment (two-way FDI) on regional environmental technology by using data from 30 provinces and cities in China from 2004 to 2017. To overcome the possible endogeneity problem of the model, the system generalized moment estimation method (system GMM) is used to estimate the model. The results show the following: First, two-way FDI could inhibit the progress of regional environmental technology. Second, the results of the regional heterogeneity test show that the development of two-way FDI interaction promotes the environmental technology in the eastern region, but inhibits the environmental technology in the central and western regions of China. Third, the heterogeneity test results of two-way FDI interactive development degree show that the two-way FDI interactive development in China promotes environmental technology in high-interactive areas, but inhibits environmental technology in low-interactive areas. Finally, the results of the phased heterogeneity test show that as China's two-way FDI interactive development gradually increases, its inhibitory effect on regional environmental technology gradually declines. Therefore, it is believed that in the future, China should further strengthen inward foreign direct investment and outward foreign direct investment, realize the benign interaction of two-way FDI, and finally promote the progress of regional environmental technology.